3(-3-3x)+4=-5
One solution was found :
x = 0
Rearrange:
Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :
3*(-3-3*x)+4-(-5)=0
Step by step solution :
Pull out like factors :
-3 - 3x = -3 • (x + 1)
Equation at the end of step 2 :
(-9 • (x + 1) + 4) - -5 = 0
Equation at the end of step 3 :
-9x = 0
Step 4 :
Solving a Single Variable Equation :
4.1 Solve : -9x = 0
Multiply both sides of the equation by (-1) : 9x = 0
Divide both sides of the equation by 9:
x = 0
One solution was found :
x = 0